1994
DOI: 10.1111/j.1365-2923.1994.tb02736.x
|View full text |Cite
|
Sign up to set email alerts
|

Communication skills in palliative care: development and modification of a rating scale

Abstract: A complex rating scale has been used to evaluate the verbal communication skills of health professionals before and after training. The scale has been modified in order to decrease the useage time, to improve its accuracy and to develop a rating tool available to teachers. This paper describes the process of the modification and discusses the consequent validation of the scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…This instrument is applied, reviewed and adapted in several studies in oncology settings [16,17,[49][50][51][52][53][54]. The method enables an utterance by utterance rating of transcribed nurse-patient encounters.…”
Section: Quantitative Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…This instrument is applied, reviewed and adapted in several studies in oncology settings [16,17,[49][50][51][52][53][54]. The method enables an utterance by utterance rating of transcribed nurse-patient encounters.…”
Section: Quantitative Researchmentioning
confidence: 99%
“…The method enables an utterance by utterance rating of transcribed nurse-patient encounters. According to some authors the need for transcription and the complexity of the coding system appear to be a time-consuming activity [50,56]. Consequently, efforts were made to develop a shorter rating scale, based upon the CRCIRM, and measuring only those behaviours that a validation study has shown to be effective for patient disclosure [17].…”
Section: Quantitative Researchmentioning
confidence: 99%
See 3 more Smart Citations